Unveiling the silent threat: A comprehensive review of Riemerella anatipestifer – From pathogenesis to drug resistance - Jinzhen Hao; Junxuan Zhang; Xiaolu He; Yefan Wang; Jinyang Su; Jiewen Long; Leyi Zhang; Zixing Guo; Yizhang Zheng; Mianzhi Wang; Yongxue Sun (Poultry Science)
Riemeralla anatipestifer, a predominant bacterium with multidrug resistance, has caused tremendous economic losses in the poultry farming industry. However, there are few studies on its identification, pathogenic mechanisms, and virulence factors and effective and systematic prevention and control strategies. The emergence and spread of antibacterial resistance has prompted increased focus on R. anatipestifer. However, studies on the mechanisms underlying gene aggregation and dissemination are lacking. This review summarizes recent studies on R. anatipestifer and explores its epidemiology, pathobiology, serotype classification, and preventive and treatment measures. Our findings illuminate the characteristics of virulence-related and drug resistance factors that have pivotal roles in the pathogenesis of R. anatipestifer infection. This study provides a comprehensive reference and guidance for in-depth research on R. anatipestifer.